Tres poemes eròtics en català i occità copiats en un cançoner rossellonès. - PRAT, ENRIC; VILA, PEP (Scripta)
We present the edition of three anonymous erotic poems from the XIXth century, two in Catalan and one in Occitan, from a manuscript preserved in the Fonds Albert Salsas (Archives Départementales des Pyrénées-Orientales, Perpignan -- ADPO) that contains the collection Obres de fra Pere by Pere Puiggarí.